Chilean Universities: Not So Tuition-free After All - de Gayardon, Ariane; Bernasconi, Andrés (International Higher Education, 2016)
In 2011, massive student demonstrations disturbed the proper functioning of universities, with students making free higher education one of their key demands. In 2013, Michele Bachelet, a socialist, was elected president - free higher education being one of her most important electoral promises. This article summarizes the "Short Tuition Free Act" of December 2015 in Chile which is supposed to be the first step toward a free tuition higher education for all. It analyses the current conditions under which students can have access to subsidized tuition and the pitfalls of the current law. It also provides critics of the current approach and questions the possibility of implementing a free for all policy.